Study on Estimation of the Gripping Force of Surgical Instruments Based on the Dynamic Model - Liu Fen; Liu Jiahao; Yun Jintian; Sang Hongqiang (Jixie chuandong)
The problem of estimating the gripping force of surgical instruments has been the focus of research on minimally invasive surgical robotic surgical instruments. During the minimally invasive surgery, excessive gripping force can cause tissue damage, and too small gripping force can make suture needles fall off and cause danger. Therefore, it is necessary to study how to estimate the gripping force of surgical instruments. According to the structural characteristics of surgical instruments, a method for estimating gripping force based on dynamic model is proposed. The dynamic model of the surgical instrument, the force and displacement transmission characteristics of the cable driven system and the direct-current motor characteristics are considered in the established model, and the relation between the surgical instrument motor current and the gripping force is obtained. The gripping force model is validated by using Matlab simulation, and the gripping force variation curve of the surgical instrument end-effector with the change of the motor current are obtained. The simulation results show that the gripping force estimation model of the surgical instrument based on the dynamic model is consistent with the actual situation, which provides a theoretical basis for the subsequent research on the gripping force security of the surgical instrument.